From Crisis to Renewal : Development Policy and Management in Africa - Hope, Kempe Ronald (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This volume deals with crisis and renewal in African development policy and management. It digs deep into, takes stock of, and thoroughly analyzes the nature, impact, and future of development policy and management on the continent. It demonstrates the failure of post-independence policy and management in most of Africa, traces the emergence and results of reform measures, and advocates the lessons of success for the rest of Africa derived from Botswana's approach to sustainable development and its achievement of economic prosperity and the maintenance of political stability and good governance. It concludes, rather optimistically, that the prospects for sustainable development are much better now than they have ever been before with the 21st century likely to be hailed as 'The African Century' - bringing with it a durable peace and sustainable growth.